2014
DOI: 10.3389/fped.2014.00116
|View full text |Cite
|
Sign up to set email alerts
|

Animal Models to Investigate the Pathogenesis of Rheumatic Heart Disease

Abstract: Rheumatic fever (RF) and rheumatic heart disease (RHD) are sequelae of group A streptococcal (GAS) infection. Although an autoimmune process has long been considered to be responsible for the initiation of RF/RHD, it is only in the last few decades that the mechanisms involved in the pathogenesis of the inflammatory condition have been unraveled partly due to experimentation on animal models. RF/RHD is a uniquely human condition and modeling this disease in animals is challenging. Antibody and T cell responses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 28 publications
1
21
0
Order By: Relevance
“…The RAV model is the only credible model currently in use to dissect the multiple mechanisms that may play a role in the immunopathogenesis of RF/RHD (47). Currently using this model we aimed to determine whether repeated exposure to different GAS M serotypes, both ‘rheumatogenic’ and ‘non-rheumatogenic’ or non-group A streptococci, are sufficient to exacerbate rheumatic carditis with symptomatology.…”
Section: Discussionmentioning
confidence: 99%
“…The RAV model is the only credible model currently in use to dissect the multiple mechanisms that may play a role in the immunopathogenesis of RF/RHD (47). Currently using this model we aimed to determine whether repeated exposure to different GAS M serotypes, both ‘rheumatogenic’ and ‘non-rheumatogenic’ or non-group A streptococci, are sufficient to exacerbate rheumatic carditis with symptomatology.…”
Section: Discussionmentioning
confidence: 99%
“…A rat model was previously developed to mimic rheumatic heart disease. [22][23][24][25][26] Histological examination of cardiac tissue in rats immunised with recombinant M5 (rM5) revealed the presence of inflammatory lesions in both the myocardium and valve tissue 22 which were akin to the histological changes observed in RF/RHD in humans. In this investigation the rat Figure 3.…”
Section: Vaccine Formulation Does Not Induce Pathology In a Lewis Ratmentioning
confidence: 99%
“…The rats were immunized as described previously. 18,22,26 Briefly, 8-week-old female Lewis rats (n D 5/group) were immunized subcutaneously on day 0 into the hock with either rM5 (500 ug), J8-DT (150 ug) or DT (150 ug) emulsified 1:1 with Complete Freund's Adjuvant (Sigma, Australia) in a total volume of 200 ul following anesthesia with isofluorane (5%) in 100% oxygen. On day 1 and 3, the rats received an intraperitoneal injection of 1 £ 10 10 whole killed Bordetella pertussis cells as an additional adjuvant.…”
Section: Vaccine Formulation Does Not Induce Pathology In a Lewis Ratmentioning
confidence: 99%
“…However, the role served by Bmi1 and BRG1 in cardiac stem cells remains unclear. It is difficult to create animal models of RHD and studying the different pathological stages of RHD remains a challenge (30). In the present study, an animal model of RHD that mimicked the pathological characteristics observed in humans with RHD was successfully developed.…”
Section: Discussionmentioning
confidence: 98%